Health communication in the Quran: Charles saunders pierce’s semiotic analysis - Abdul Basit (Penerbit Universiti Kebangsaan Malaysia, 2017)
Health communication that has been developed is dominated by Western point of view in which it is lack of religious values; while among the Muslim scholars, the conception of health communication has not been developed systematically. It is because the health communication is a discipline that has been started to develop during the contemporary era and the health communication practices have not shown any significant developments. By the development of science and information technology, the role of health communication starts to have significant role in Muslim society. This paper investigates the Quranic terms about the health communication and their ideologies. It is conducted by implementing library research of the verses of the Quran and their interpretation as the main data. Then the data were analyzed using Charles Saunders Pierce’s (1839-1914) semiotic approach through the analysis of semantics, syntactic, and pragmatics. The results show that the terms of quwwah, ithma'anna, thaharah, tazkiyyah, maridh, adza, rijsun, saqiyyun, and syifa are the terms that have the meaning of health. After conducting Pierce’s semiotic analysis, those terms express health and communication elements in which those terms are orderly structured into a series of verses whose meanings are arranged holistically and systematically. So, pragmatically, it contains ideology or guidance than can be developed in terms of health communication.